1998
DOI: 10.1111/j.1468-3156.1998.tb00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Exercise and Health of Adults with Mild and Moderate Learning Disabilities

Abstract: The aim of the study was to evaluate the cardiorespiratory fitness, levels of obesity, daily levels of physical activity and barriers to a physically active lifestyle in a group of 24 adults with mild and moderate learning disabilities (aged 2 3 4 7 years, mean age 34). The efficacy of two community-based exercise intervention programmes for the group was also evaluated. The results showed that overall 50% of the men and 70% of the women were overweight, of whom 57% of the men and 100% of the women were obese.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 8 publications
6
46
1
1
Order By: Relevance
“…Similar findings have been reported in a few studies from England using the criteria of at least 12 bouts of 20 minutes of moderate (Ͼ5 and Ͻ7.5 kcal/ min) to vigorous (Ն7.5 kcal/min) activity occurring over 4 weeks [Messent et al, 1998b;Robertson et al, 2000;Emerson, 2005]. This threshold had been identified as offering some protection against coronary heart disease [Department of Health, 1995] and the proportion of participants meeting this criterion ranged from 4 to 20%.…”
Section: Physical Activity Behaviorsupporting
confidence: 78%
See 2 more Smart Citations
“…Similar findings have been reported in a few studies from England using the criteria of at least 12 bouts of 20 minutes of moderate (Ͼ5 and Ͻ7.5 kcal/ min) to vigorous (Ն7.5 kcal/min) activity occurring over 4 weeks [Messent et al, 1998b;Robertson et al, 2000;Emerson, 2005]. This threshold had been identified as offering some protection against coronary heart disease [Department of Health, 1995] and the proportion of participants meeting this criterion ranged from 4 to 20%.…”
Section: Physical Activity Behaviorsupporting
confidence: 78%
“…Problems with acquiescence and comprehension in self-report research with this population have been well-documented [Bogdan and Taylor, 1994;Finlay and Lyons, 2001]. Proxy respondents (e.g., caregivers) are typically used as self-report resources to assess physical activity in this group [Messent et al, 1998b[Messent et al, , 1999Robertson et al, 2000Draheim et al, 2002a,, 2002b], but there are some concerns regarding the reliability of this approach because secondary sources may not accurately report primary source behavior [Finlay and Lyons, 2001]. This is particularly true for individuals with MR who reside in less controlled settings (e.g., supported living versus institution).…”
Section: Self-reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, training in motor skills enables a person to experience, explore, and understand the world around them (Reimer & Siemonsma-Boom, 2013;Schellingerhout, Smitsman, & Cox, 2005) as well as increasing selfcontrol and autonomy. However, several studies have demonstrated that people with intellectual disability have significantly fewer opportunities to experience movement and/or have lower rates of physical activity than those without disability (Draheim, Williams, & McCubbin, 2002;Emerson, 2005;Hilgenkamp, Reis, van Wijck, & Evenhuis, 2012;Lahtinen, Rintala, & Malin, 2007;Messent, Cooke, & Long, 1998;Robertson et al, 2000;Temple, Frey, & Stanish, 2006). These studies indicate that the rate of physical activity varies with the level of impairment: in general, when the intellectual disability is more severe the level of physical inactivity increases (Emerson, 2005;Peterson, Janz, & Lowe, 2008;Robertson et al, 2000).…”
Section: Introductionmentioning
confidence: 92%
“…4 Severity levels for ID are typically categorised by broad intelligence quotient (IQ), alongside the required deficits in independent living skills, into mild (IQ [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69], moderate (IQ [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], severe and profound (IQ < 20) ID. 5 Acknowledging the wide variation that exists between individuals with ID, typical abilities suggested for each category are outlined in Table 1 [based on World Health Organization (WHO) International Classification of Diseases, Tenth Edition (ICD-10)].…”
Section: Definition Of Intellectual Disability and Case Identificationmentioning
confidence: 99%